Romance and reproduction are socially costly - Burton-Chellew, MN; Dunbar, RIM (American Psychological Association, 2015)
Close social relationships provide the primary source of many important, beneficial forms of social support. However, such relationships can deteriorate without regular contact and communication and therefore entail maintenance costs. Consequently, the number of close network members that an individual can afford to maintain is likely to be constrained by factors such as the time they have to devote to servicing such relationships. New romantic relationships, despite providing large evolutionary benefits in the form of increased reproduction, may be unusually costly in this respect because the individual’s attention is intensely focused on the partner, and, ultimately, their offspring. This change of focus may impact on other relationships, reducing the availability of help from kin and friends. We used an Internet sample of 540 respondents to test and show that the average size of support networks is reduced for individuals in a romantic relationship. We also found approximately 9% of our sample reported having an “extra” romantic partner they could call on for help, however these respondents did not have an even smaller network than those in just 1 relationship. The support network is also further reduced for those who have offspring, however these effects are contingent on age, primarily affecting those under the age of 36 years. Taking into account the acquisition of a new member to the network when entering a relationship, the cost of romance is the loss of nearly 2 members. On average, these social costs are spread equally among related and nonrelated members of the network.